Fat levels analysis of mantis shrimp (harpiosquilla raphidea) in the interidal zone in the waters of the state of Suli, Central Maluku - Wa Ode Zulfiana; Alwi Smith; Muh Nur Matdoan; Hasan Tuaputty (BIOEDUPAT: Pattimura Journal of Biology and Learning, 2022)
Mantis shrimp (Harpiosquilla raphidea) is a type of predatory shrimp. Mantis shrimp is a type of crustacean with high nutritional value, but it is not widely known by the people of Eastern Indonesia, especially the people of Suli. This research was conducted in May 2021 and was tested for fat content at the Basic Chemistry Laboratory, Pattimura University, Ambon, with the type of descriptive research. This study used the Soxhlet method, which is the method used for fat extraction with N-Hexane as a fat solvent. The results of this study showed that the fat content of white mantis shrimp was 3.33% and black mantis shrimp was 5.56%. The fat content of white mantis shrimp is 3.33% and black mantis shrimp is 5.56%.